The Distribution of Transplanted Umbilical Cord Mesenchymal Stem Cells in Large Blood Vessel of Experimental Design With Traumatic Brain Injury. Issue 6 (September 2017) - Dong, Hua-Jiang; Shang, Chong-Zhi; Li, Gang; Niu, Qing; Luo, Yue-Chen; Yang, Yue; Meng, Hui-Peng; Yin, Hui-Juan; Zhang, Hai-Xia; Zhao, Ming-Liang; Lin, Ling
Abstract : Abstract: The authors aim to track the distribution of human umbilical cord mesenchymal stem cells (MSCs) in large blood vessel of traumatic brain injury -rats through immunohistochemical method and small animal imaging system. After green fluorescent protein (GFP) gene was transfected into 293T cell, virus was packaged and MSCs were transfected. Mesenchymal stem cells containing GFP were transplanted into brain ventricle of rats when the infection rate reaches 95%. The immunohistochemical and small animal imaging system was used to detect the distribution of MSCs in large blood vessels of rats. Mesenchymal stem cells could be observed in large vessels with positive GFP expression 10 days after transplantation, while control groups (normal group and traumatic brain injury group) have negative GFP expression. The vascular endothelial growth factor in transplantation group was higher than that in control groups. The in vivo imaging showed obvious distribution of MSCs in the blood vessels of rats, while no MSCs could be seen in control groups. The intravascular migration and homing of MSCs could be seen in rats received MSCs transplantation, and new angiogenesis could be seen in MSCs-transplanted blood vessels.